Temporal analysis of actions to control Chagas disease in Sergipe, Brazil (1998-2015) (Research, Society and Development, 2020)
Objective: Temporal analysis of actions to control Chagas disease from 1998 to 2015 and its impact on the state of Sergipe, Brazil. Methods: Retrospective study based on secondary data obtained from the Chagas Disease Control Program (CDCP) (positive species, captured triatomine species, infection index and chemical control) and the of Housing Improvement Project (material resources, construction progress and monitoring) for evaluation of the actions of these programs in the eight Sergipe territories. A temporal analysis was performed through the model Joinpoint Regression Analysis. Results: Differences in coverage rates were observed of the program in the different territories the municipalities located in the Alto Sertão region being the most attended. Six species of triatomines were collected with reduction in the number of specimens at the end of the period, found mainly for the coastal area of ​​the State. The highest infection rate was found in Panstrongylus lutzi There was important resources for housing improvement in all territories, however, implementation was satisfactory for most. Conclusion: Despite the weaknesses observed in the Program, there was important advances in the control of Chagas disease. However, it is necessary to resume activities, considering that there are necessary conditions for the disease to spread due to vectors and reservoirs that have not yet been studied.